"Satan’s Synagogue". Presences of Heresy in Leopoldo María Panero’s Poetry (Castilla. Estudios de Literatura, 2011)
Leopoldo María Panero’s poetry is set as a constant claiming of transgression in every order, from Moral to Epistemological. In the following lines we will study one particular transgression. We are speaking about heresy, as an image of the subversion of institutionalized knowledge, in Panero’s work. For this we drew three main lines, the most remarkable in Panero’s texts. The first one deals with the Gnostic heresy, which has its splendor in the first centuries of Christianity; after that Millenarianism will be studied; finally, we will see the huge treatment that witchcraft receives in Panero’s poetry.